Seismic Performance of Reinforced Concrete Frames with Clay and Lightweight Brick Infill Walls Using Response Spectrum Analysis - Rabbani, Nauval (Jurnal Teknik Sipil, 2025)
Indonesia faces a high earthquake risk due to its location at the convergence of major tectonic plates, necessitating earthquake-resistant building design that accounts for both structural and non-structural components, including infill walls. This study evaluates the effect of infill wall materials—clay bricks and lightweight bricks—on the seismic response of a four-story reinforced concrete frame building located on soft soil in Pekalongan City. The analysis was performed using the response spectrum method in ETABS. Two structural models were developed by representing the infill walls as uniformly distributed dead loads on beams, with each load corresponding to the wall material. The results show that the use of lightweight bricks reduces lateral and vertical forces at the ground floor by approximately 9–11% and decreases the maximum inter-story drift by up to 7.6% compared to clay bricks. In addition, the lightweight brick model exhibits a shorter fundamental vibration period, indicating increased structural stiffness due to reduced mass. All models satisfy the mass-participation requirements specified in the Indonesian seismic code. These findings indicate that lightweight bricks provide a more efficient alternative for infill walls and improve the seismic performance of mid-rise buildings in earthquake-prone regions.